Design of a serious game learning mechanism for the implementation of ISO 22000:2018 in the swallow’s nest industry - Anang, Kukuh Adisusilo; Teguh Pribadi Ikshan (International Journal of Advanced Technology and Engineering Exploration, 2024)
A food safety management system standard, such as the International Organisation for Standardisation (ISO) 22000:2018, is required for food items like swallow’s nests to be approved for entry into most countries. Although ISO 22000:2018 is already well known to many businesses, its manual documentation rules are onerous. As a result, a digital approach is needed to expedite the adoption of this standard. If changes in user behavior do not support a digital approach in the form of an information system, then the process may become more complex. To increase user participation, a computational flow incorporating a learning idea is required. A serious game framework that emphasizes enjoyment and has a clear objective—implementing the ISO 22000:2018 flow—is used to construct a digitalization of ISO 22000:2018 that is based on understanding serious game mechanics. Employing research using swallow’s nest management information system (SN-MIS), serious game design software engineering is demonstrated using a hierarchical finite state machine, which has three superstates: initial sorting, processing, and final sorting. On the serious game learning mechanism side, there are learning elements in the form of game actions, learning activities, and instructional activities. Gamification is achieved within the game action elements. The user interface plays a major role in gaining users’ attention to inform them about the system being used and influence their behavior to facilitate the effective implementation of ISO 22000:2018.